The Impacts of Climate and Wildfire on Ecosystem Gross Primary Productivity in Alaska. Issue 6 (8th June 2021) - Madani, Nima; Parazoo, Nicholas C.; Kimball, John S.; Reichle, Rolf H.; Chatterjee, Abhishek; Watts, Jennifer D.; Saatchi, Sassan; Liu, Zhihua; Endsley, Arthur; Tagesson, Torbern; Rogers, Brendan M.; Xu, Liang; et al.
Abstract: The increase in wildfire occurrence and severity seen over the past decades in the boreal and Arctic biomes is expected to continue in the future in response to rapid climate change in this region. Recent studies documented positive trends in gross primary productivity (GPP) for Arctic boreal biomes driven by warming, but it is unclear how GPP trends are affected by wildfires. Here, we used satellite vegetation observations and environmental data with a diagnostic GPP model to analyze recovery from large fires in Alaska over the period 2000–2019. We confirmed earlier findings that warmer‐than‐average years provide favorable climate conditions for vegetation growth, leading to a GPP increase of 1 Tg C yr −1, contributed mainly from enhanced productivity in the early growing season. However, higher temperatures increase the risk of wildfire occurrence leading to direct carbon loss over a period of 1–3 years. While mortality related to severe wildfires reduce ecosystem productivity, post‐fire productivity in moderately burned areas shows a significant positive trend. The rapid GPP recovery following fires reported here might be favorable for maintaining the region's net carbon sink, but wildfires can indirectly promote the release of long‐term stored carbon in the permafrost. With the projected increase in severity and frequency of wildfires in the future, we expect a reduction of GPP and therefore amplification of climate warming in this region. Plain Language Summary: We analyzed the indirect impact of wildfires in Alaska on the amount of carbon fixed during photosynthesis, which is known as ecosystem gross primary productivity (GPP). Satellite observations and our remote sensing GPP model confirmed earlier findings of increasing vegetation growth in warmer‐than‐average years. On the other hand, risk of wildfire occurrence is higher during the warmer years, which leads to direct vegetation loss, and as result reduction in ecosystem carbon uptake over a period of 1–3 years. We also observed rapid GPP recovery following fires, but severe wildfires are expected to reduce the GPP and therefore amplification of climate warming in this region due to the release of long‐term stored carbon in the permafrost. Key Points: Gross primary productivity (GPP) data in Alaska show increasing trends in the last two decades due to increased carbon uptake in the early growing season Temperature enhances plant productivity in the early growing season and increases the risk of wildfire occurrences Ecosystem GPP is negatively affected by wildfires, but shows fast recovery following less severe wildfires